2006
DOI: 10.5424/srf/2006151-00955
|View full text |Cite
|
Sign up to set email alerts
|

Germination capacity and temperature dependence in Mediterranean species of the Balearic Islands

Abstract: To test the germination capacity and its temperature dependence in Mediterranean plants, sixteen species representative of a diversity of habitats of the Balearic Islands were selected. The percentage of germination, the half-response time and the dormancy period of these species were studied at three alternating temperatures: 5-15°C, 10-20°C and 15-25°C. Large differences were found among species in all three parameters studied. The influences of the temperature incubation in germination behaviour depended st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Nevertheless, both species showed low germination activity at high temperatures ranging from 15-25°C. This is in agreement with other studies that have also reported low germination rates in Mediterranean species such as Pistacia lentiscus, Phlomis italica and Urtica atrovirens subsp.bianorii [21,25,29]. This could be due to presence of dormancy mechanisms by which plants have adapted to unpredictable environments [43], including the Mediterranean climate.…”
Section: Seed Germination Seedling Emergence and Regeneration Abilitysupporting
confidence: 82%
See 3 more Smart Citations
“…Nevertheless, both species showed low germination activity at high temperatures ranging from 15-25°C. This is in agreement with other studies that have also reported low germination rates in Mediterranean species such as Pistacia lentiscus, Phlomis italica and Urtica atrovirens subsp.bianorii [21,25,29]. This could be due to presence of dormancy mechanisms by which plants have adapted to unpredictable environments [43], including the Mediterranean climate.…”
Section: Seed Germination Seedling Emergence and Regeneration Abilitysupporting
confidence: 82%
“…Both Rhamnus species showed a longer dormancy period and T 50 under 15-25ºC than in the other treatments (5-15ºC and 10-20ºC). In contrast, a shorter dormancy period and T 50 have been reported for some Mediterranean species, such as Stipa tenacissima [30], Ceratonia siliqua [31], Diplotaxis ibicencis, Limonium magallufianum and Limonium gibertii at the same temperature regimes (5-15ºC, 10-20ºC and 15-25ºC) [25]. Differences between species in seed germination, dormancy period and T 50 are expected in Mediterranean ecosystems, since many of them show different types and degrees of dormancy [24].…”
Section: Seed Germination Seedling Emergence and Regeneration Abilitymentioning
confidence: 98%
See 2 more Smart Citations
“…Germination was defined as the visible emergence of the radicle through the seed coat (Maguire 1962, Galmés et al 2006). …”
Section: Germination Testmentioning
confidence: 99%